2023
DOI: 10.1002/ecs2.4356
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the occupancy of Chinese pangolins (Manis pentadactyla) suggest a highly specialized ecological niche

Abstract: The Chinese pangolin is a critically endangered and biologically unique species, yet information on its status, distribution, and habitat preferences is still scarce in Nepal, which limits effective conservation action. This study identified the current burrow density status, distribution pattern, and important habitat parameters associated with Chinese pangolin distribution in Nepal through opportunistic field surveys. Fifty‐four belt transects were examined for the presence of pangolin burrows. For each acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 42 publications
5
14
0
Order By: Relevance
“…This study revealed that pangolins are strongly associated with moderate canopy cover, which is in accordance with the results of Bhandari and Chalise (2014), Dorji et al (2020), andDhami et al (2023). A possible reason for this might be that soils below moderate canopy cover are dry and consist of relatively undecomposed leaf litter and a greater amount of dead twigs and branches (Bhandari and Chalise, 2014), whereas the soil where the crown cover is above 60% is moist with a thick layer of decomposing leaf litter, which is negatively associated with the availability of ants and termites.…”
Section: Distribution and Habitat Preferencesupporting
confidence: 92%
See 3 more Smart Citations
“…This study revealed that pangolins are strongly associated with moderate canopy cover, which is in accordance with the results of Bhandari and Chalise (2014), Dorji et al (2020), andDhami et al (2023). A possible reason for this might be that soils below moderate canopy cover are dry and consist of relatively undecomposed leaf litter and a greater amount of dead twigs and branches (Bhandari and Chalise, 2014), whereas the soil where the crown cover is above 60% is moist with a thick layer of decomposing leaf litter, which is negatively associated with the availability of ants and termites.…”
Section: Distribution and Habitat Preferencesupporting
confidence: 92%
“…This study revealed that forest is the preferred habitat of pangolin, with burrows mostly recorded in S. robusta followed by S. wallichii forests. This is in accord with other studies, which report burrows mostly in forested areas (Gurung, 1996;Acharya, 2001;Bhandari and Chalise, 2014;Katuwal et al, 2017Dhami et al, 2023). In forests, termites are very abundant (Ackerman et al, 2009), which could account for the high pangolin occurrence (Swart et al, 1999).…”
Section: Distribution and Habitat Preferencesupporting
confidence: 92%
See 2 more Smart Citations
“…Nepal has two of the eight extant species of pangolin found in the world: the Indian Pangolin Manis crassicaudata & Chinese Pangolin Manis pentadactyla (Suwal et al 2020;Dhami et al 2023). The Indian Pangolin is cryptic and has complex biology (Mohapatra et al 2021), i.e., a single one is born in the breeding season and is a diet specialist, which makes it vulnerable.…”
Section: Introductionmentioning
confidence: 99%